Demand and Supply in the Talent Market - Vathy, Veronika (International Journal of Engineering and Management Sciences, 2018)
In Hungary, the emergence of a talent market for organizations is due to the growing demand for talented workers. The talent’s definition, the exploration of the factors affecting the talent market’s demand and his supply are necessary to the overview. With the emergence of the talent market, we will also carry out an important analysis of the changes in the labor market in Hungary as well as the shortage of labor shortages. In the labor market today, different generations are present, who have different expectations for their employer and work environment. The lack of skilled workers is attempted by organizations with different methods. One of these is the ability of companies to become a talent-magnet, resulting in a higher number of employees in their area of activity. In areas where labor shortages are high, more and more attention is paid to automating processes. During the research, I worked on the related literature and studies to determine the factors influencing the talent market.